1998
DOI: 10.1007/s002620050484
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies reactive with the protein core of MUC1 mucin are present in ovarian cancer patients and healthy women

Abstract: Antibodies reactive with peptide epitopes on the core protein of MUC1 epithelial mucin have been demonstrated in some patients with adenocarcinomas. Because these epitopes can be exposed on MUC1 in the serum of healthy women, we measured concentrations of MUC1-reactive antibodies in the serum of healthy pregnant and non-pregnant women, and in patients with benign and malignant ovarian tumours. Antibodies were measured in an enzyme-linked immunosorbent assay utilising a synthetic peptide corresponding to a 105-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 21 publications
6
47
0
2
Order By: Relevance
“…[33][34][35][36] In this regard, it is of note that specifically blocking the function of a complement regulatory protein without coadmin- In conclusion, the data presented fully support the hypothesis that reversing the effects of complement regulatory proteins expressed on a tumor cell surface will allow more effective immunemediated clearance of tumor cells and improve prospects for successful immunotherapy. The results justify further research and development of strategies to inhibit or downregulate complement regulatory proteins on tumor cells.…”
Section: Discussionsupporting
confidence: 55%
“…[33][34][35][36] In this regard, it is of note that specifically blocking the function of a complement regulatory protein without coadmin- In conclusion, the data presented fully support the hypothesis that reversing the effects of complement regulatory proteins expressed on a tumor cell surface will allow more effective immunemediated clearance of tumor cells and improve prospects for successful immunotherapy. The results justify further research and development of strategies to inhibit or downregulate complement regulatory proteins on tumor cells.…”
Section: Discussionsupporting
confidence: 55%
“…We and others demonstrated that MUC1-specific antibodies are associated with a better prognosis in breast, pancreatic, lung, and ovarian cancer (23)(24)(25)(26). Similarly, the presence of T cells in tumors has been associated with better prognosis in lung, ovarian, and colon cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 96%
“…Anti-MUC1 antibodies have been described and correlated with a more favorable prognosis (2)(3)(4)(5) showing that patients generate immunity against MUC1 produced by their tumors and defining MUC1 as a tumor-associated antigen and candidate for cancer vaccines (6). Anti-MUC1 antibodies are also found in healthy individuals, especially in women during pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%